Deconstructing Phatic Particles in Javanese: A Case Study of the Film Tilik (2018) - Inayatul Luthfiyyah (Sutasoma : Jurnal Sastra Jawa, 2025)
This study aims to describe the forms and functions of phatic particles in Javanese as used in the film Tilik (2018), directed by Wahyu Agung Prasetyo. Phatic particles are linguistic elements that function to maintain social relationships and express the attitudes of both speakers and interlocutors. These particles reflect the values of politeness, familiarity, and social harmony as expressed in everyday speech. The research employs a qualitative descriptive method with a pragmatic approach, drawing on Kridalaksana’s (2008) theory of phatic functions and Leech’s (1983) framework of practical functions. Data were obtained from Tilik's (2018) transcript and analyzed based on contextual and pragmatic meanings. The findings reveal seven types of phatic particles used by the characters, namely to/ta, lha ya, lho ya, kok, mbok, and je. Among them, to/ta and lho ya are the most frequently used, functioning to emphasize information and build mutual understanding. The particle kok expresses surprise or mild disagreement, while mbok is used to give advice or polite admonition. The particle je serves as a gentle marker of emphasis and social closeness. Overall, phatic particles play a crucial role in maintaining politeness, strengthening social solidarity, and representing the communicative, respectful, and harmonious character of Javanese society. This study affirms that language is not only a medium for conveying messages but also a vehicle for shaping cultural values and social identity.